The Views of Environmental Health Engineering Graduates Working in Mazandaran Province, on Compliance of Curriculum Content with Occupational Requirements - Hatameh Babaie; Zahra Geraili; Fateme Asgharzadeh; Hosseinali Asgharnia (Babol University of Medical Sciences, 2018)
BACKGROUND AND OBJECTIVE: Due to the wide scope of the roles and activities of environmental health experts and in response to the extensive educational needs of experts, the content of educational materials should be designed according to these professional roles and activities in order to carry out the responsibilities associated with this organizational post. Therefore, the aim of this study was to investigate the level of coordination of syllabus of Environmental Health Engineering (EHE) BS with job requirements from the viewpoints of postgraduates in Mazandaran province. METHODS: This descriptive cross-sectional study was conducted in health centers of Mazandaran province in 2016. Totally, 80 students were randomly selected among EHE graduates using cluster sampling method. A researcher-made questionnaire whose reliability was evaluated based on internal consistency and Cronbach's alpha coefficient and validity was confirmed by experts, was used to collect data. Data were analyzed using SPSS22 and descriptive statistics (frequency, percentage of frequency). FINDINGS: Among available courses, "food inspection and control" (from the viewpoints of 56.3%) had the most applicable in terms of content and practical skills and "pump motor in water and wastewater facilities (from the viewpoints of 75%)" and "utilization and maintenance of water and wastewater facilities (from the viewpoints of 75%)" had the least application. CONCLUSION: Some syllabi of EHE BS's courses are not fully coordinated with job requirements of this field. Therefore, it is necessary to review the syllabus of this curriculum in order to achieve educational goals.